Humoral Response to mRNA-1273 SARS-CoV-2 Vaccine in Peritoneal Dialysis Patients: Is Boostering After Six Months Adequate? - Beilhack, Georg; Monteforte, Rossella; Frommlet, Florian; Reindl-Schwaighofer, Roman; Strassl, Robert; Vychytil, Andreas (Frontiers in Medicine, 2022)
In dialysis patients the humoral response to anti-SARS-CoV-2 vaccines is attenuated and rapidly declines over time. However, data on the persistence of the immune response in peritoneal dialysis (PD) patients are scarce, particularly after a third (booster) dose with mRNA-1273 vaccine. In this prospective cohort study, we report anti-SARS-CoV-2 antibody levels in PD patients before and after the third dose of mRNA-1273 vaccine. Six months after the second dose, anti-SARS-CoV-2 antibodies were detected in all patients (n=34), but substantially declined in 31 of 34 patients (4.5-fold, median=192 BAU/mL, p=1.27x10-9). In accordance with government regulations, a third dose of mRNA-1273 vaccine (50 µg) was given to 27 PD patients six months after the second dose which induced a significant increase of anti-SARS-CoV-2 antibody titers (58.6-fold, median=19405 BAU/mL, p=1.24x10-29). A mixed model analysis showed that a lower Davies Comorbidity Score and a higher GFR were associated with higher antibody titers (p=0.03 and p=0.02). The most common adverse events after the third dose were pain at the injection site (77.8%) and fatigue (51.9%). No hospitalizations were reported. In conclusion, six months after the second dose of mRNA-1273 vaccine, anti-SARS-CoV-2 antibodies substantially decreased in PD patients, whereas a well-tolerated third dose induced a robust humoral response. Our data suggest that the administration of a booster dose within a shorter interval than six months would be beneficial in PD patients in order to maintain high anti-SARS-CoV-2 antibody levels and assure protection from severe COVID-19 disease.